Possibilities of implementing smart contracts in the rent-a-car sector - Tošić Violeta; Radulović Zoran; Borković Milana; Tošić Teodora (Trendovi u Poslovanju)
The paper presents the possibilities of applying blockchain technology and smart contracts in the rent-a-car sector of tourism. Special attention is given to the implementation possibilities of smart contracts in the rent-a-car industry. The application of smart contracts in this sector can be a key factor contributing to the sustainable development of tourism by promoting ecological practices and responsible behavior among travelers.